Engineering dual-functional VB2 nanoparticles in MgH2 for highly efficient hydrogen storage. (August 2021) - Pang, Yuepeng; Wang, Yufang; Yang, Junhe; Zheng, Shiyou
Abstract: Introduction of reactive additives into MgH2 is a promising strategy for improving the hydrogen storage performances, but the inevitable formation of inert by-products degrades the effective capacity. In this work, a dual-functional additive, amorphous VB2 nanoparticles, is introduced into MgH2 by ball milling, which significantly lowers the working temperatures by over 120 °C without a huge capacity loss. VB2 reacts with MgH2 to in-situ form V and MgB2 during ball milling and dehydrogenation, in which V remains unchanged during cycling and MgB2 is hydrogen-storage-active that can absorb hydrogen. In addition, V acts as an active catalyst, which provides nucleation sites and decreases the apparent activation energy. Therefore, both the products from this VB2 additive can make contributions to the hydrogen storage performances, showing a dual-functional effect. Graphical abstract: Image 1 Highlights: Amorphous VB2 nanoparticles were successfully prepared via a solid-state reaction. VB2 modified MgH2 exhibits a 120 °C reduction in hydrogen desorption temperature. V as an active catalyst is in-situ formed from the reaction between VB2 and MgH2 . The in-situ formed MgB2 is hydrogen-storage-active and can further absorb hydrogen.